A brief review on the history of human functional near-infrared spectroscopy (fNIRS) development and fields of application - Ferrari, Marco; Quaresima, Valentina (NeuroImage (Orlando, Fla.), 2012)
This review is aimed at celebrating the upcoming 20th anniversary of the birth of human functional near-infrared spectroscopy (fNIRS). After the discovery in 1992 that the functional activation of the human cerebral cortex (due to oxygenation and hemodynamic changes) can be explored by NIRS, human functional brain mapping research has gained a new dimension. fNIRS or optical topography, or near-infrared imaging or diffuse optical imaging is used mainly to detect simultaneous changes in optical properties of the human cortex from multiple measurement sites and displays the results in the form of a map or image over a specific area. In order to place current fNIRS research in its proper context, this paper presents a brief historical overview of the events that have shaped the present status of fNIRS. In particular, technological progresses of fNIRS are highlighted (i.e. from single-site to multi-site functional cortical measurements (images)), introduction of the commercial multi-channel systems, recent commercial wireless instrumentation and more advanced prototypes. ► The paper celebrates the 20th anniversary of functional fNIRS. ► Events that have shaped the present status of fNIRS are reported. ► fNIRS methodology has undergone consistent improvements over the years. ► The application of fNIRS in Medicine and basic research have been increasing. ► Technological development will augment fNIRS application in adults and infants.